2020
DOI: 10.21203/rs.3.rs-42148/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

General public’s knowledge and practices on face mask use during the COVID-19 pandemic: a cross-sectional exploratory survey from Dharan, Nepal

Abstract: Background: Measures to prevent and control coronavirus disease-19 (COVID-19) include regular handwashing, physical distancing and covering mouth and nose using a face mask, thereby reducing spread of droplets. Use of facemask is considered as a cheap, effective and safe method with minimum disruption in day-to-day life. This study assessed the knowledge and practice of Nepalese general public on face mask use during lockdown period of COVID-19 pandemic. Method: A cross-sectional study using a self-developed, … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…Of them, Q 25 -Q 30 were important to assess their mask-wearing behaviour and among them, 31% adjusted their mask by touching the front portion, 27% remove their mask when they cough/sneeze and 14% speak after removing their mask. This shows their poor behaviour which is similar to a cross-sectional study conducted by Alam et al (2020), where they questioned pharmacists in Nepal, regarding their knowledge about mask use and mask-wearing behaviour. On average, 30% of their respondents had poor behaviour, where 58% touched their mask while wearing and 21% mask users failed to cover their nose, mouth and chin 7 .…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Of them, Q 25 -Q 30 were important to assess their mask-wearing behaviour and among them, 31% adjusted their mask by touching the front portion, 27% remove their mask when they cough/sneeze and 14% speak after removing their mask. This shows their poor behaviour which is similar to a cross-sectional study conducted by Alam et al (2020), where they questioned pharmacists in Nepal, regarding their knowledge about mask use and mask-wearing behaviour. On average, 30% of their respondents had poor behaviour, where 58% touched their mask while wearing and 21% mask users failed to cover their nose, mouth and chin 7 .…”
Section: Discussionsupporting
confidence: 81%
“…This shows their poor behaviour which is similar to a cross-sectional study conducted by Alam et al (2020), where they questioned pharmacists in Nepal, regarding their knowledge about mask use and mask-wearing behaviour. On average, 30% of their respondents had poor behaviour, where 58% touched their mask while wearing and 21% mask users failed to cover their nose, mouth and chin 7 . Also regarding the hours of use, 22% of respondents in our study used the same mask for more than 4 hours (longer than recommended).…”
Section: Discussionsupporting
confidence: 81%
“…In another study, though most of the participants were aware about proper mask wearing (78%) and avoiding touching the mask (42.3%) as important measures for prevention, still only one-fifth (20%) used facemask in public. (18) In our study, commonly cited reasons by the participants for not wearing mask properly or no mask at all, were breathing difficulty, mask being uncomfortable among other reasons. Public needs to be assured that mask usage may cause little discomfort for a short time but its benefits are manifold.…”
Section: Discussionmentioning
confidence: 54%
“…20 The post intervention result comes in agreement with a study conducted in China in year of 2020 which reported that people who watched the health education videos were more likely to wear masks and follow health related behaviors. 21 Regarding barriers to face mask use revealed by our study, the most important barriers were expensive medical masks, uncomfortable in hot and humid environment, leads to difficult communication, the unpleasant appearance of face masks, forgetfulness, feel of embarrassment as it might cause people to criticize me about being in public while ill, leads to headache and/or breathing difficulties. Similar barriers were recorded in a previous study conducted to assess the benefits and burdens of wearing face masks in schools during the current Corona pandemic.…”
Section: Discussionmentioning
confidence: 78%